Identification Sub-Surface Structure and Sediment Depth Estimation at the Proposed Indonesian New Capital City - Yan Adi Segoro; Relly Margiono (Department of Physics, Sebelas Maret University, 2025)
In this study, we employ high-resolution GGMplus gravity satellite data and three-dimensional geological modeling to ascertain sediment thickness and subterranean structures in East Kalimantan, designated as Indonesia's prospective capital. The region's sedimentary basins, specifically the Kutai Basin with up to 14 kilometers of Tertiary sedimentary rocks, are pivotal in assessing seismic risk due to their potential to amplify seismic activity. Through Fourier transformation and power spectrum analysis, we discern the Simple Bouguer Anomaly (SBA) across the region, revealing an inverse relationship between SBA values ranging from -5 mGal to 145 mGal and topographical elevation. The Mangkalihat Peninsula showcases pronounced gravity anomalies corresponding to a complex geological matrix, including a carbonate platform and an extension of the Palukoro Fault system. The three-dimensional inversion modeling, across a 29,000 meters by 27,000 meters grid, identifies varying rock densities from 2.3 g/cm³ to 2.65 g/cm³, and delineates predominant rock types such as igneous granite, claystone, limestone, and sandstone. This is further validated by resistivity measurements, aligning with geological maps. The average regional depth estimates for sediment layers are -15274.93 meters for North-South transects and -13409.25 meters for West-East transects, with residual depth estimates suggesting sediment thickness up to -1988 meters. These granular insights enhance the geological model of East Kalimantan, providing a nuanced understanding of its geophysical framework and informing the developmental blueprint for Indonesia's future capital city.